1989
DOI: 10.1002/mrm.1910090115
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metabolism in man after acute stroke: New observations using localized proton NMR spectroscopy

Abstract: Localized proton NMR spectroscopy at 1.5 T using stimulated echoes has been applied to study metabolic alterations in the postischemic phase of patients with acute cerebral infarction. A complete depletion of N-acetyl aspartate in the area of infarction has been observed in a patient studied 4 days after stroke. This finding was paralleled by a dramatic increase in the concentration of lactic acid to about 16 mM within the lesion, indicating continued anaerobic glycolysis. The diluting effect of the edema has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(97 citation statements)
references
References 11 publications
(2 reference statements)
6
90
0
1
Order By: Relevance
“…This effect was more pronounced in ROIs, where normalized NAA levels were initially more dramatically reduced. NAA concentrations in the brain are high and it is mainly localized to neurons (35); therefore, it has been considered as a neuronal marker (36). Reduction of NAA was often ascribed to neuronal loss but today it is clear that alternative explanations should be considered, as recovery in NAA was reported.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was more pronounced in ROIs, where normalized NAA levels were initially more dramatically reduced. NAA concentrations in the brain are high and it is mainly localized to neurons (35); therefore, it has been considered as a neuronal marker (36). Reduction of NAA was often ascribed to neuronal loss but today it is clear that alternative explanations should be considered, as recovery in NAA was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MRS in medical diagnosis of human neurological disease has also been described (Danielsen and Ross, 1999;Gillard et al, 2005;Lin et al, 2005). In human and animal studies, proton MRS and MRI have consistently demonstrated large increases in lactate levels, and significant decreases in NAA levels in ischemic brain tissue several hours after onset (Bruhn et al, 1989b;Di Costanzo et al, 2003;Fenstermacher and Narayana, 1990;Franke et al, 2000;Graham et al, 1994). However, there is a paucity of published information concerning the early response of neuronal NAA metabolism in human stroke patients.…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 96%
“…15 - 19 The decrease appears to occur mainly between 6 (in one patient) and 24 hours after the clinical incident. The loss of NAA seems to be greater in the central than in the outer part of the VOI, suggesting a heterogeneous distribution of NAA within the infarcted area as visualized by MRI.…”
Section: Discussionmentioning
confidence: 99%